Conventional versus doxorubicin-eluting beads transarterial chemoembolization for unresectable hepatocellular carcinoma: A tertiary medical centre experience in Malaysia - Abdul Rahman F.; Naidu J.; Ngiu C.S.; Yaakob Y.; Mohamed Z.; Othman H.; Jarmin R.; Elias M.H.; Abdul Hamid N.; Mohd Mokhtar N.; Raja Ali R.A. (Asian Pacific Organization for Cancer Prevention, 2024)
Indexed by Scopus